Party affiliation rather than former occupation: The background of central bank governors and its effect on monetary policy - Matthias Neuenkirch; Florian Neumeier (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
In this paper, we analyze the relationship between certain characteristics of incumbent central bank governors and their interest-rate-setting behavior. We focus on (i) occupational backgrounds, (ii) party affiliation, and (iii) experience in office and estimate augmented Taylor rules for 20 OECD countries and the period 1974-2008. Our findings are as follows. First, the tenures of central bank governors who are affiliated with a political party are characterized by a relatively dovish monetary policy stance, irrespective of their partisan ideology. Second, party affiliation appears to be more important than occupational background, i.e., all bankers with(out) a party affiliation behave very similarly to each regardless of their specific occupational background. Third, party members react significantly less to inflation and more to output the longer they stay in office.
Keywords: E31; E43; E52; E58; 330; Central Bank Governors; Monetary Policy; Occupation; Partisanship; Taylor Rules